DAMPAK PERKEMBANGAN PEMBAYARAN NON TUNAI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Rukmana, Rismawati Dewi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aimed to find out impact of cashless transaction and economic growth in Indonesian. The author uses economic growth as the dependent variable and include variables of cashless transaction as an independent variable. The author uses quantitative research methods and using error correction model with time series data.The results showed that the variable of consumstion and cash ratio is not significant in short term and long term on economic growth. Variable cash and non cash ratio is significant and positive in short term, while in long term is not significant on economic growth. Variable the value of ATM/Debet transaction growth and the value of credit card transaction growth are not significant in short term and long term on economic growth.Keywords: Cashless Transaction, Economic Growth, Macroecomic, Error Correction Model (ECM).